Fe3O4/Fe2O3/Fe nanoparticles anchored on N-doped hierarchically porous carbon nanospheres as a high-efficiency ORR electrocatalyst for rechargeable Zn–air batteries - Wang, Yali; Gan, Ruihui; Liu, Hao; Dirican, Mahmut; Chengbiao Wei; Chang, Ma; Shi, Jingli; Zhang, Xiangwu (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
The advancement of electrocatalysts using non-precious metals with excellent catalytic ability and durability for the oxygen reduction reaction (ORR) remains an enormous challenge. Transition metal–nitrogen–carbon (M–N–C) materials become target products with great development and application prospects for the ORR in new electrochemical energy storage and conversion devices. Herein, a simple preparation procedure of N-doped hierarchically porous carbon nanospheres loaded with Fe3O4/Fe2O3/Fe nanoparticles (Fe–CNSs–N) is developed by direct annealing of an Fe-doped quinone-amine polymer in an NH3/Ar atmosphere. Due to the integration of large specific surface area, hierarchically porous structure, and Fe3O4/Fe2O3/Fe nanoparticles, Fe–CNSs–N presents a half-wave potential of 0.835 V vs. RHE, which is 7 mV more positive than that of a commercial Pt/C catalyst in an alkaline medium. It also exhibits outstanding long-cycle durability as well as methanol endurance, superior to the Pt/C catalyst. Compared to the zinc–air battery based on Pt/C, the Fe–CNSs–N-based battery presents a higher open-circuit potential of 1.54 V, steadier discharge–charge cycle performance and an outstanding maximum power density of 106.8 mW cm−2. The excellent electrocatalytic performances make Fe–CNSs–N a promising substitute for Pt/C noble-metal catalysts in rechargeable Zn–air batteries.